CORPORATE GOVERNANCE, FIRM CHARACTERISTICS, AND FIRM VALUE: THE MEDIATING ROLE OF TAX AVOIDANCE IN INDONESIAN ENERGY COMPANIES - Suryadi; Wahyudi, Ilham; Z, Rico Wijaya (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
This research seeks to enhance understanding of the implications of corporate governance, firm characteristics, and tax avoidance on firm value, especially in the context of Indonesian energy companies. The energy sector holds significant strategic value for Indonesia’s economy; yet, there are gaps in research concerning the nexus of governance, corporate characteristics, tax planning, and firm value. This research focuses on 216 firm-year records from energy companies listed on the Indonesian Stock Exchange from 2021-2024. Analysis is conducted through Partial Least Squares Structural Equation Modelling (PLS-SEM) using the SmartPLS 4 software. Corporate governance is operationalized through the metrics of independent commissioners, board size, managerial ownership, and institutional ownership, and corporate characteristics are firm size, profitability, and leverage. The proxy for tax avoidance is the effective tax rate, while firm value is represented by Tobin’s Q. Findings indicate that corporate governance and firm characteristics both have an impact on tax avoidance. However, corporate governance and tax avoidance were found to exert no significant influence on firm value. Tax avoidance does not mediate the relationship between corporate governance and firm value or between firm characteristics and firm value. The results imply that, in valuing firms, energy sector investors in Indonesia are more concerned with the fundamental financial performance of firms than with the governance structures of firms and the firms' tax-planning activities.